Tiktok sebagai Media Edukasi Parenting: Studi Pemaknaan Fatherhood dalam Akun @babeheji - Qur'ani, Afifah Izzati; Putra, Fajar Dwi (Universitas Muhammadiyah Magelang, 2024)
Indonesia is known as the third largest fatherless country in the world. This study aims to find out how the public perceives the role of fathers in the context of fatherhood as conveyed through the content of Tiktok @babeheji. This study uses a descriptive qualitative method, which focuses on exploring the public's understanding of social media content, especially that related to the role of fathers in child rearing. The researcher conducted observations through the comments found on the TikTok account @babeheji. The results of the study indicate that the TikTok content @babeheji successfully conveys the message to the public about the importance of the father's role in raising a child. The appreciation expressed in the comment section serves as evidence that the content on the @babeheji TikTok account is not only entertaining but also serves as an aspiration for building an ideal family. This study makes an important contribution to mass communication theory and reception theory by demonstrating how social media content can influence audience perceptions and behaviors regarding the importance of the father's role and the role of social media in disseminating positive social values.